2014
DOI: 10.1542/peds.2014-0832
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Bullying and Risk of Depression, Anxiety, and Self-Harm: A Prospective Cohort Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Recent reviews suggest that children bullied by siblings are at increased risk of internalizing symptoms. It is not known whether being bullied by a sibling increases risk of psychiatric disorders such as depression, anxiety, and self-harm. WHAT THIS STUDY ADDS:Using a large, community-based birth cohort, we found that being bullied by a sibling is prospectively associated with a doubling in the odds of both depression and self-harm at 18 years in young adults. abstract OBJECTIVES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
175
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(207 citation statements)
references
References 45 publications
25
175
2
5
Order By: Relevance
“…Among 786 children who reported bullying by a sibling several times a week, 12.3% had depression, 16.0% anxiety and 14.1% had self-harmed. 3 Children frequently bullied by siblings when they were 12 years old were more likely to have depression (odds ratio [OR] 2.16), self-harm (OR 2.56) and experience anxiety (OR 1.83) when they were 18 years old than controls. Assuming the relationship is causal, sibling bullying could account for 13.0% of cases of depression and 19.3% of cases of self-harm.…”
Section: A Safe Havenmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 786 children who reported bullying by a sibling several times a week, 12.3% had depression, 16.0% anxiety and 14.1% had self-harmed. 3 Children frequently bullied by siblings when they were 12 years old were more likely to have depression (odds ratio [OR] 2.16), self-harm (OR 2.56) and experience anxiety (OR 1.83) when they were 18 years old than controls. Assuming the relationship is causal, sibling bullying could account for 13.0% of cases of depression and 19.3% of cases of self-harm.…”
Section: A Safe Havenmentioning
confidence: 99%
“…Assuming the relationship is causal, sibling bullying could account for 13.0% of cases of depression and 19.3% of cases of self-harm. 3 Sibling relationships, unlike peer groups, tend to endure through a child's development and there are few opportunities to escape. Again, victims of sibling bullying are more likely to be bullied by their peers.…”
Section: A Safe Havenmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, verificam-se frequentemente problemas de baixa autoestima (Wiehe, 1998), ansiedade (Caffaro & ConnCaffaro, 1998), depressão e automutilação em jovens adultos (Bowes, Wolke, Joinson, Lereya, & Lewis, 2014), comportamentos delinquentes (Button & Gealt, 2014), entre outros.…”
Section: Introductionunclassified
“…Sibling relationships marked by elevated levels of conflict and hostility can result in a myriad of troublesome longer term consequences including conduct problems, delinquent behaviour (Bank, Patterson, & Reid, 1996;Criss & Shaw, 2005), and other externalising and internalising problems such as depression, anxiety, and self-harm (Buist, Deković, & Prinzie, 2013;Kim, McHale, Crouter, & Osgood, 2007;Tucker, Finkelhor, Turner, & Shattuck, 2013). Bowes, Wolke, Joinson, Lereya, and Lewis (2014) demonstrated that being bullied by a sibling doubles the risk of depression and self-harm at 18 years of age. Wayward or dysfunctional sibling relationships, therefore, can serve as a precursor to individuals setting sail on a problematic developmental trajectory.…”
Section: Why Study Sibling Relationships?mentioning
confidence: 99%